2013
DOI: 10.1371/journal.pone.0065847
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Reed Warblers Need Intact Trigeminal Nerves to Correct for a 1,000 km Eastward Displacement

Abstract: Several studies have shown that experienced night-migratory songbirds can determine their position, but it has remained a mystery which cues and sensory mechanisms they use, in particular, those used to determine longitude (east–west position). One potential solution would be to use a magnetic map or signpost mechanism like the one documented in sea turtles. Night-migratory songbirds have a magnetic compass in their eyes and a second magnetic sense with unknown biological function involving the ophthalmic bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 68 publications
(96 reference statements)
7
99
1
Order By: Relevance
“…Our findings suggest that there are magnetosensory structures associated with V1 and are thus in agreement with data in Mora et al [25], Heyers et al [26] and Kishkinev et al [27]. In these studies, nerve sectioning led to significant decreases in the birds' ability to detect and/or to react to magnetic field changes [25,27], or found a correlation between the magnetic field stimulation and neuronal responses at brain level [26]. Thus, the most parsimonious explanation for the present data is that V1 carries magnetic field information.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings suggest that there are magnetosensory structures associated with V1 and are thus in agreement with data in Mora et al [25], Heyers et al [26] and Kishkinev et al [27]. In these studies, nerve sectioning led to significant decreases in the birds' ability to detect and/or to react to magnetic field changes [25,27], or found a correlation between the magnetic field stimulation and neuronal responses at brain level [26]. Thus, the most parsimonious explanation for the present data is that V1 carries magnetic field information.…”
Section: Discussionsupporting
confidence: 94%
“…V1 is the only non-olfactory nerve innervating the upper beak in pigeons [24]. Mora et al [25] could show that homing pigeons trained to distinguish between the presence and absence of a strong magnetic anomaly lost this ability after sectioning V1; Heyers et al [26] showed that constantly changing magnetic fields (CMFs) activate the trigemino-recipient brainstem complex in a migratory songbird species, the European robin, and that this activation disappeared when either the magnetic field was compensated (ZMF) or V1 was cut; and Kishkinev et al [27] showed that Eurasian reed warblers were unable to compensate for a 1000 km east-west displacement when V1 was cut. In addition to these studies where V1 was actually cut, a large number of studies using anaesthetics applied onto the upper beak also reported significant effects [28 -30, but see critique in 9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the ability to discriminate the presence and absence of a magnetic anomaly with changes in intensity and inclination was abolished following the sectioning of this nerve in homing pigeons (Mora et al, 2004). Whilst a possible role of the trigeminal nerve during homing by pigeons in Italy at distances of up to 105 km has been dismissed (Gagliardo et al, 2006;Gagliardo et al, 2009), several recent studies have investigated the role of the ophthalmic branch of the trigeminal nerve in transmitting magnetic information to the brain in migratory and non-migratory birds such as European robins (Erithacus rubecula) (Heyers et al, 2010) and Pekin duck (Anas platyrhynchos domestica) (Freire et al, 2012) and its role in correcting for displacement during migration in, for example, reed warblers (Acrocephalus scirpaceus) (Kishkinev et al, 2013). Two recent studies by Wu and Dickman (Wu and Dickman, 2011;Wu and Dickman, 2012) have also shown involvement of pigeon trigeminal neurons in magnetoreception, as well as recorded neuronal responses in the pigeon's brainstem in response to changes in direction, intensity and polarity of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our recent study with migrating Eurasian reed warblers in spring suggests that in this species, an intact trigeminal nerve is needed for a compensatory orientation response after a 1000 km eastward displacement ( Fig. 6; Chernetsov et al 2008;Kishkinev et al 2013). Even though this study did not address the nature of sensory input needed for the compensatory navigational response in reed warblers (Chernetsov et al 2008), it suggested that the trigeminal nerve transmits map-related input to the brain, whether it be of olfactory, magnetic or another nature.…”
Section: Magnetic Navigationmentioning
confidence: 87%
“…Indeed, in some cases, displaced birds' initial flights were in seemingly random directions before more consistent directions were chosen (Thorup et al 2007; circling at release site for the first minutes described in many pigeon experiments : Gould 1980;Wallraff 2005). However, there are reports that even captive birds can perform navigation that cannot be explained by this hypothesis (Chernetsov et al 2008;Kishkinev et al 2013).…”
Section: Magnetic Navigationmentioning
confidence: 99%